Processing Issues and the Characterization of Soft Electrochemical 3D Sensor. (20th November 2015) - Ragones, Heftsi; Schreiber, David; Inberg, Alexandra; Berkh, Olga; Kósa, Gábor; Shacham-Diamand, Yosi
Abstract: In this work we present the process and characterization issues of 3D electrochemical sensor made on a polymeric substrate using through-substrate via contacts filled with a conductive polymer. In this paper we highlight and demonstrate the main purpose of this architecture for a "touch" sensing applications. The chip consists of a PDMS substrate comprising an electrochemical cell with two gold electrodes (working and counter) and an Ag/AgCl quasi-reference electrode. In the present 3D architecture the electrodes are located on one side of the substrate while the contacts are located at the back side, allowing electrical signals to flow vertically to the potentiostat and signal processing units. The electrical communication between the bio-chip front and backside is enabled by conducting vias fabricated by cast molding. The via-contacts are filled with conductive PDMS containing 60 wt% graphite powder. Electrochemical characterization of the chip is carried by measuring the redox behavior ferricyanide/ferrocyanide couple in a cyclic voltammetry analysis. The 3D sensor exhibits stable voltammetric signatures in repeated tests. Enzymatic activity of alkaline phosphatase in two cell lines was detected and quantified by chronoamperometric assay. These results showing that the described system is suitable for non-invasive diagnostics both for in-vitro & in-vivo applications.